2013
DOI: 10.1371/journal.pone.0076273
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Olfactory Exposure to Non-Insecticidal Agrochemicals on Bumblebee Foraging Behavior

Abstract: Declines in bumblebee populations have led to investigations into potential causes – including agrochemical effects on bumblebee physiology. The indirect effects of agrochemicals (i.e. behavior modulation) have been postulated, but rarely directly tested. Olfactory information is critical in mediating bumblebee-floral interactions. As agrochemicals emit volatiles, they may indirectly modify foraging behavior. We tested the effects of olfactory contamination of floral odor by agrochemical scent on foraging acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…As of June 2019 Home Depot's website listed 333 products under plant care geared for disease control and fertilization. At least one prior study has shown that the scent of a consumer lawn product is capable of modifying bumblebee foraging behavior in the lab [10]-but piecewise testing of 333 products is an intractable amount of work for the academic community and agrochemical producers are unlikely to take up the cause. Agrochemical odor pollution is not confined to consumer products; commercial agrochemicals may also be problematic [10].…”
Section: Understanding Generalization and Discrimination Behavior Of mentioning
confidence: 99%
See 3 more Smart Citations
“…As of June 2019 Home Depot's website listed 333 products under plant care geared for disease control and fertilization. At least one prior study has shown that the scent of a consumer lawn product is capable of modifying bumblebee foraging behavior in the lab [10]-but piecewise testing of 333 products is an intractable amount of work for the academic community and agrochemical producers are unlikely to take up the cause. Agrochemical odor pollution is not confined to consumer products; commercial agrochemicals may also be problematic [10].…”
Section: Understanding Generalization and Discrimination Behavior Of mentioning
confidence: 99%
“…At least one prior study has shown that the scent of a consumer lawn product is capable of modifying bumblebee foraging behavior in the lab [10]-but piecewise testing of 333 products is an intractable amount of work for the academic community and agrochemical producers are unlikely to take up the cause. Agrochemical odor pollution is not confined to consumer products; commercial agrochemicals may also be problematic [10]. Using the CWB-method to calculate angular shifts due to agrochemical scent-pollution could identify products that shift odors into a 'zone of concern', namely outside the identified generalization zone.…”
Section: Understanding Generalization and Discrimination Behavior Of mentioning
confidence: 99%
See 2 more Smart Citations
“…These agrochemicals can contaminate both pollen and nectar, posing an ecological and economic risk for beneficial interactions (Chauzat et al, 2006;Gill et al, 2012;Krupke et al, 2012;Pettis et al, 2013). For instance, exposure to and consumption of fungicides can have detrimental effects on beneficial macroorganisms such as bees, affecting larval development (Mussen et al, 2004), foraging behavior (Sprayberry et al, 2013), and driving mortality through both direct and indirect pathways (Pettis et al, 2013;Bernauer et al, 2015). Although evidence is mounting on the detrimental effects of agrochemicals on macroorganisms, less attention has been paid to non-target microorganisms that may also benefit crop yield (but see Alvarez-P erez et al, 2016;Bartlewicz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%